TRANSFORMASI PENANGANAN COVID-19: DARI KOMUNIKASI KRISIS KE KOMUNIKASI RISIKO - Dila Novita; Adi Susila; Elvira Suryani; Muhammad Fadil; Muhammad Yunus (Jurnal Ilmu Komunikasi PROGRESSIO, 2021)
President Jokowi made public communication related to Covid-19 on March 2, 2020. Government communication in this crisis has become a challenge because since that moment the public's response and assessment began. In the early stages, public communication carried out by the government was still in the perspective of Crisis Communication, various kinds of confusion of information began to emerge, the public became doubtful about the truth of the scattered data. Furthermore, the World Health Organization recommends handling Covid-19 from the perspective of Risk Communication which is considered more comprehensive and effective in building communication to the public. For this reason, this study intends to evaluate Government Public Communication in Handling Covid-19 in a Risk Communication Perspective. This study uses qualitative research methods, applies a phenomenological research design by searching for data through observation and in-depth interviews through the application of purposive sampling by determining key informants from the government, communication experts, and the community. Secondary data collection is also carried out through journals, websites, webinar presentations, YouTube, social media, and online media portals. The results showed that the transformation of Government Public Communication from Crisis Communication to Risk Communication was carried out not only because of a request from the World Health Organization as an evaluation of government-run communication but also as a form of improving the Indonesian government's communication strategy in handling covid-19 which at first it was considered not alert and fast in preventing the spread of the Covid-19 pandemic in Indonesia. In addition, the success of Risk Communication cannot be separated from the active engagement of the community in helping the government produce and disseminate information content that is attractive, trustworthy, and accountable.